Differences in propelling efficiency between competitive and triathlon swimmers - Toussaint, H. M. (Medicine & Science in Sports & Exercise, 1990)
Two highly trained groups; competitive swimmers (N = 6); and triathletes (N = 5), were compared to evaluate the significance of the propelling efficiency as a performance determining factor in swimming. Using regression equations the groups were compared at equal power input. The groups did not differ in gross efficiency, stroke frequency, and work per stroke. There was a difference in distance per stroke (1.28 m vs 0.99 m), and mean swimming velocity (1.11 m.s-1 vs 0.90 m.s-1). The difference in swimming speed between the two groups can be explained by the fact that the competitive swimmers can use a much higher proportion of their power output to overcome drag (44 W vs 30 W). At the same time the competitive swimmers expend less power in moving water backwards (28 W vs 39 W). This difference in apportionnement of the power output can be characterized as the propelling efficiency (power used to overcome drag/total power output). Mean (±SD) propelling efficiency for the competitive swimmers was 62 ± 6% but only 44 ± 4% for the triathletes. The relation between swimming velocity and gross efficiency, propelling efficiency, power input and drag provides a valuable approach to the understanding of swimming.